Investigation of Factors Affecting the Production and Properties of Maize Cob-Particleboards - Sekaluvu, Lawrence; Tumutegyereize, Peter; Kiggundu, Nicholas (Waste and biomass valorization, 2015)
The aim of this research was investigating the factors that affect the properties and production of particle- boards from maize cobs. The particleboards were produced at three different levels of resin content (125, 188, and 250 g) while using particles in the size ranges of 1.13 to\3.35 mm and 3.35–8 mm. Compaction ratio, pressing pressure, and mass of maize cob particles were production variables which were considered during the experiment. The maize cob particleboards were pressed under a pressure of 13 MPa and were left to cure for 17 h while holding at a pressure of 10 MPa. Properties of maize cob particleboards such as density, modulus of rupture (MOR), modulus of elasticity (MOE), water absorption, thickness swelling and linear expansion were investigated. The densities of maize cob particleboards ranged from 386 ± 49.96 to 723 ± 34.65 kg/m3 , which were comparable to the particleboard densities of 590 and 800 kg/m3 of wood product industry. Maize cob particleboards produced using particles of size 3.35–8 mm presented a higher density as compared to other maize cob particleboards. The modulus of elasticity for maize cob particleboards was in the range 5.89 ± 6.00 to 61.82 ± 10.09 MPa, while the modulus of rupture ranged from 0.32 ± 0.14 to 1.50 ± 0.16 MPa, thus maize cob particle- boards could be used as ceiling boards and wall claddings. Particleboards produced from particles of size in the range 1.13–8 mm presented better mechanical properties (MOE and MOR) as compared to other particleboards. The maize particleboards showed poor properties to moisture and thus applicable to interior applications. From ANOVA analysis, particle size and resin content significantly affected (p B 0.01) the properties of maize cob particleboards.
Keywords: Maize cob particleboard; Particle size Resin content; Maize cob particleboard properties